If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 2) + -4(x + -1) = 24 Reorder the terms: 5(2 + x) + -4(x + -1) = 24 (2 * 5 + x * 5) + -4(x + -1) = 24 (10 + 5x) + -4(x + -1) = 24 Reorder the terms: 10 + 5x + -4(-1 + x) = 24 10 + 5x + (-1 * -4 + x * -4) = 24 10 + 5x + (4 + -4x) = 24 Reorder the terms: 10 + 4 + 5x + -4x = 24 Combine like terms: 10 + 4 = 14 14 + 5x + -4x = 24 Combine like terms: 5x + -4x = 1x 14 + 1x = 24 Solving 14 + 1x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 1x = 24 + -14 Combine like terms: 14 + -14 = 0 0 + 1x = 24 + -14 1x = 24 + -14 Combine like terms: 24 + -14 = 10 1x = 10 Divide each side by '1'. x = 10 Simplifying x = 10
| 39(g-8)=-9 | | 5+8x=50+1.5 | | 120x=1500 | | 4(a+7)=40 | | -80y=320 | | 20=8c-4 | | 9e-4=77 | | 2(y-5)-1(y+6)=-4 | | -240=8y | | 2x-12=27 | | -8y=124 | | 4x+1/3=2/3 | | 18n-5= | | x-48=4x+7 | | 9e-6=75 | | 0.6y=60 | | 3x^2-100=0 | | 5(x^2+.4)=3 | | x^4-4x^3+5x^2-2x-2=0 | | 2(3n-1)-1(n+6)=7 | | 0.75x=15 | | (5x-1)(x+2)=0 | | (N+2)(n+5)=0 | | x*x-18=-3x | | 24x-6(3x-5)=11(4x+1) | | 0=2(c^2)-8c+8 | | (x-6)(x-3)=0 | | 3*(t+36)=150 | | 3a=6 | | 16y=8 | | 16.8-u=6u | | 425252663627272663736362+838279823893298389327848624684863684= |